The Interest Rate Pass-Through in Malaysia: An Analysis on Asymmetric Adjustment - Tang, Maggie May-Jean; Puah, Chin Hong; Liew, Venus Khim-Sen (Universiti Putra Malaysia, 2015)
The interest rate channel is the primary and most important mechanism for policymakers. Knowledge of the pass-through of interest rates has allowed policymakers to draw conclusions on how fast and to what extent a shock in policy rates are transmitted to retail rates. This paper investigates the pass-through effect of policy rate on retail rates in Malaysia. Asymmetric threshold autoregressive (TAR) and momentum threshold autoregressive (MTAR) proposed by Enders and Siklos (2001) are employed in the study. Over the period of January 1987 to December 2014, the policy rate was found to be an incomplete pass-through to deposit and lending rates. Based on the asymmetric analysis, we discover the asymmetry effects in the response of retail rates to the change of policy rate. In addition, we find downward rigidity in both deposit and lending rates.